Effect Effect of the Poly-Unsaturated Fatty Acids (Omega-3) on Postpartum Fertility and Energy Balance of Dairy Cows in Syria (Journal of Hama University, 2019)
Twenty dairy cows, /3-7/ years old, were used to determine the effect of the PUFA -Polyunsaturated Fatty Acids- (Omega-3) injection during the postpartum period on reproduction performance and energy balance of dairy cows in Syria.Cows were divided randomly into two groups (10 cows per group): First group (G1) injected IM /10/ ml of Omega-3 in /30/ and /45/ days postpartum period. Second group or control group (G2) no received any treatment of Omega-3 during the postpartum period.Ovaries of cows were examined /20, 40, 60, and 80/ days from calving by transrectal ultrasonography to determine follicular development, estrus synchronization and pregnancy average. Blood samples were collected at /15, 30, 45 and 60/ days postpartum to determine serum concentrations of Glucose, β-hydroxybutyrate, Cholesterol, Total Protein, and Progesterone.We observed no significant differences (P>0.05) among treatments for serum concentrations of metabolites (Glucose, β-hydroxybutyrate, Cholesterol and Total Protein), while we observed significant difference for serum concentration of progesterone hormone after /45/ days postpartum (P